Dating Miss Maude Adams, as “L’Aiglon” - Leslie Anne Anderson (Panorama, 2018)

(untitled)
While organizing the 2017 permanent collection reinstallation at the Utah Museum of Fine Arts, Mythmaking and Truth-Telling: American and Regional Art, I made discoveries in the artist’s papers at the Archives of American Art that allow us to precisely date Miss Maude Adams, as “L’Aiglon” and to better contextualize the painting within the intellectual milieu of its creation.